2008
DOI: 10.1111/j.1365-2621.2007.01683.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional potential and functional properties of tempe produced from mixture of different legumes. 1: Chemical composition and nitrogenous constituent

Abstract: Fermented foods such as Tempe represent a technological alternative for a great variety of legumes and combination of them to improve their nutritional quality and to obtain edible products with palatable sensorial characteristics. The chemical composition, carbohydrate fraction and nitrogenous constituents were investigated for individual different legumes, i.e. faba bean; lupine, chickpea; peas and their mixture before and after fermentation by Rhizopus oligosporus. Tempe had a higher (P < 0.05) protein and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In lupin (Lupinus mutabilis and Lupinus campestris), tempeh fermentation diminished the quinolizidine alkaloid content, which is a toxic factor (Jiménez-Martínez, Hernández-Sánchez, & Dávila-Ortiz, 2007). In soy, chickpea, pea, faba bean, and lupin, tempeh fermentation can greatly reduce or diminish undigestible and flatulence-causing oligosaccharide content, including alpha-galactooligosaccharides, stachyose, raffinose, and verbascose (Nassar, Mubarak, & El-Beltagy, 2008;Ruiz-Teran & Owens, 1999;Tewari, 2002;van der Riet et al, 1987). In dark common bean, tempeh fermentation can decrease the levels of stachyose, raffinose, and verbascose by 57%, 67%, and 53%, respectively (Starzynska-Janiszewska et al, 2015).…”
Section: On Toxins and Antinutrientsmentioning
confidence: 99%
“…In lupin (Lupinus mutabilis and Lupinus campestris), tempeh fermentation diminished the quinolizidine alkaloid content, which is a toxic factor (Jiménez-Martínez, Hernández-Sánchez, & Dávila-Ortiz, 2007). In soy, chickpea, pea, faba bean, and lupin, tempeh fermentation can greatly reduce or diminish undigestible and flatulence-causing oligosaccharide content, including alpha-galactooligosaccharides, stachyose, raffinose, and verbascose (Nassar, Mubarak, & El-Beltagy, 2008;Ruiz-Teran & Owens, 1999;Tewari, 2002;van der Riet et al, 1987). In dark common bean, tempeh fermentation can decrease the levels of stachyose, raffinose, and verbascose by 57%, 67%, and 53%, respectively (Starzynska-Janiszewska et al, 2015).…”
Section: On Toxins and Antinutrientsmentioning
confidence: 99%
“…The technological functional properties performed by legumes such as soy bean, lentil, fababean, pea and cowpea, among others, includes high molecular weight, solubility in a wide range pH, emulsification, viscosity, gelification and foaming (Baniel, Caer, Colas, & Gueguen, 1992;Maltais, Remondetto, & Subrade, 2008;Pedrosa, Trisciuzzi, & Ferreira, 1997;Rangel, Domont, Pedrosa, & Ferreira, 2003;Sosulski et al, 1976). Studies have demonstrated several applications of legume proteins in the development of varied food products, such as cakes, sausages, gelled food, fermented food and others (Geervani, Vimala, Pradeep, & Devi, 1996;Gomez, Oliete, Rosell, Pando, & Fernandez, 2008;Nassar, Mubarak, & El-Beltagy, 2008;Nunes, Raymundo, & Sousa, 2006). However, these properties were not much explored in the development of microparticulate controlled release systems for incorporation into functional foods.…”
Section: Introductionmentioning
confidence: 99%
“…Amarteifio and Moholo (1998), Bower et al (1988) and Keegan and Van Staden (1981) all investigated the protein content of marama beans and found that it ranges from 30 to 39% dm. The protein content is comparable to or higher than most other legume seeds such as dry peas, chick peas, lentils, kidney beans, cowpea and lupine with contents between 20 and 40% dm (Gueguen, 1983;Nassar et al, 2008) and equals that of soybeans (33-46% dm) (Belitz et al, 2004;Gueguen, 1983;Hymowitz et al, 1972). The protein composition of marama beans is largely dominated by glutamic and aspartic acid as well as tyrosine (Bousquet, 1981;Bower et al, 1988;Dubois et al, 1995).…”
mentioning
confidence: 96%